Older people as victims and perpetrators of crime - Di Lorito, Claudio; Völlm, Birgit (Oxford University Press, 2018)
Older people are at a higher risk of becoming the victims of crime than of being the perpetrators of it, given the added vulnerability that comes with aging. This chapter examines crime in relation to old age. The first section presents data around older people as victims of crime, and further discusses different types of abuse against older people, which, in the presence of intensive care needs and carer burden, may be perpetrated within the family or in residential and institutional settings. The second section of the chapter examines older people as the perpetrators of crime. In particular, it describes how older offenders are dealt within the justice system, it presents data on the growing population of older offenders in prisons and in forensic psychiatric services and report on whether the unique needs of older offenders are being met in these settings.